Elimination of Specific miRNAs by Naked 14-nt sgRNAs - Takahashi, Masayuki; Elbarbary, Reyad A.; Abe, Mayumi; Sato, Mari; Yoshida, Tetsuo; Yamada, Yoji; Tamura, Masato; Nashimoto, Masayuki (PLOS ONE, 2012)
tRNase ZL-utilizing efficacious gene silencing (TRUE gene silencing) is a newly developed technology to suppress mammalian gene expression. TRUE gene silencing works on the basis of a unique enzymatic property of mammalian tRNase ZL, which is that it can recognize a pre-tRNA-like or micro-pre-tRNA-like complex formed between target RNA and artificial small guide RNA (sgRNA) and can cleave any target RNA at any desired site. There are four types of sgRNA, 5′-half-tRNA, RNA heptamer, hook RNA, and ∼14-nt linear RNA. Here we show that a 14-nt linear-type sgRNA against human miR-16 can guide tRNase ZL cleavage of miR-16 in vitro and can downregulate the miR-16 level in HEK293 cells. We also demonstrate that the 14-nt sgRNA can be efficiently taken up without any transfection reagents by living cells and can exist stably in there for at least 24 hours. The naked 14-nt sgRNA significantly reduced the miR-16 level in HEK293 and HL60 cells. Three other naked 14-nt sgRNAs against miR-142-3p, miR-206, and miR-19a/b are also shown to downregulate the respective miRNA levels in various mammalian cell lines. Our observations suggest that in general we can eliminate a specific cellular miRNA at least by ∼50% by using a naked 14-nt sgRNA on the basis of TRUE gene silencing.